Development of Educaplay Learning Media Based on Problem Based Learning in Elementary School Students' Science Learning - Milda Ayu; Yeni Erita; Mega Adyna Movitaria (Postgraduate, University of Mataram, 2025)
The research started from the results of observations, the problem found at SD 27 Anak Air and SD 11 Lubuk Buaya Experiment and SD 02 Lubuk Buaya is that teachers tend to rely on the lecture method and textbooks, so students are less actively involved in the learning process. This makes students quickly feel bored and difficult to understand abstract concepts in IPAS. This research uses the type of development research. The test subjects were fifth grade teachers and fifth grade students of SDN 11 Lubuak Buaya and SDN 27 Siswa Air. This research procedure uses ADDIE development steps, namely: Analysis, design, development, implementation, evaluation. The results showed that the overall average score for validation of Educaplay Learning Media Based on Problem Based Learning was 38.3 including in the very valid category. From the aspects assessed, the value for the material is 3 with a very valid category. From the linguistic aspect, the average score is 3 with a very valid category, and from the media aspect, the average score is 3 with a valid category. The average percentage of respondents' assessment of Problem Based Learning-based Educaplay learning media is in the very practical category, namely with a practicality percentage of 90.48% and 85.71%. The assessment of the effectiveness sheet, obtained with an average assessment of 85.24, was declared effective for the development of Problem Based Learning-based Educaplay learning media.